John A. MacDonald : the Young Politician, The Old Chieftain. - Creighton, Donald Grant, 1902-1979 (University of Toronto Press, 2018)
"Sir John A. Macdonald's flamboyant personality dominated Canadian public life from the years preceding Confederation to the end of the nineteenth century, and the political structures and national policies which developed under his leadership continue to shape public issues today. Creighton's first volume takes Macdonald from his childhood and early years as a young lawyer in Kingston, Ontario, through his swift rise in political life to positions of influence, to the great achievement of uniting the colonies of British North America in Confederation. The second volume traces Macdonald's often tumultuous subsequent career in the context of a growing and often recalcitrant nation. He was Prime Minister from 1867 to 1873 and then again from 1878 until his death in June, 1891. The evocative epilogues with which Creighton concludes each volume are widely recognized as having a place among the great passages of literary prose." "P. B. Waite's introduction to this new one-volume republication provides an illuminating account of the impact that Creighton and his biography of Macdonald had on a whole generation of historians and readers."--Jacket